Klossiella equi Infection in an Immunosuppressed Horse: Evidence of Long-Term Infection - Lora R. Ballweber; Deanna Dailey; Gabriele Landolt (Case Reports in Veterinary Medicine)
A 13-year-old quarter horse gelding presented with a history of hematuria of approximately 1-year duration, anemia, weight loss over the previous six months, and bilateral nasal discharge of 2-week duration. It was determined that hematuria was most likely caused by the coccidian parasite Klossiella equi. Additional case workup suggested a diagnosis of pituitary pars intermedia dysfunction. Confirmatory testing was declined by the owners and the horse was discharged on medical therapy. Despite initial improvement after discharge, the horse developed unresolving sinusitis approximately 1 year later and was euthanized. Necropsy confirmed the presence of an adenoma of the pars intermedia of the pituitary gland, supporting the initial diagnosis. Additional findings included multiple developmental stages of K. equi present in the kidneys. This finding demonstrates infections with K. equi can be chronic in nature and supports the association of increased severity of klossiellosis and impaired immune function.